Tracing the growth of crossbred village (kampung) chickens from hatch till maturity. - Engku Ahmed, Engku Azahan (Malaysian Society of Animal Production, 2011)
Two popular strains of Malaysian crossbred kampung chickens were utilized for the purpose of gathering fundamental growth information, from hatch till the age of sexual maturity at 22 weeks. These birds comprised equal number of males and females. For both strains and sexes, similar sigmoid growth curves and patterns were exhibited. A phase of accelerated growth observed reached a point of inflection (POI) at the ages of between 8 and 9 weeks. The POI was coincident with maximum growth rate which then started to decline until maturity. Male birds were significantly superior to females from week 8 onwards, the superiority being most apparent between weeks 9 and 15 when significant differences in body weight gains were also observed.